Financial inclusion-exclusion paradox: How banked adults become unbanked again - Peterson K. Ozili (Financial Internet Quarterly, 2021)
This paper analyses how financially included adults might become unbanked again. Agents of financial inclusion incorporate economic and social constraints in the delivery of formal financial services. These constraints limit the ability of poor banked adults to use basic financial services to the fullest. The constraints affect agents of financial inclusion positively and affect customers negatively up to a point where the marginal benefit of being financially included is negative for poor customers. When the marginal benefit of using formal financial services becomes negative, the affected banked adults may discontinue using their formal accounts or exit the formal finan-cial sector when they can no longer bear the negative effect of social and economic constraints that hinder their ability to enjoy basic financial services to the fullest.
Keywords: G2; G21; O16; 330; financial inclusion; financial institutions; financial exclusion; banked adults; formal accounts; paradox; access to finance; households; constraints